Utilizing artists’ sense of place from environmental aesthetic experiences in natural resources conservation planning in Masbate City, Philippines - Asilum, Jofer B.; Jago-on, Karen Ann B. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2025)
Rooted in the growing discourse on the applications of cultural ecosystem services in attaining sustainable development, this study evaluates artists' sense of place from environmental aesthetic experiences as an approach to natural resources conservation planning in Masbate City, the Philippines. Given that sense of place strengthens environmental values and influences support for conservation, this research investigates how artists' perceptions shaped by environmental aesthetics can inform conservation efforts, not only through their art, but also their potential roles as key actors in conservation planning. This study specifically aimed to 1) explain artists' sense of place, 2) examine how environmental aesthetics contribute to making a place aesthetically remarkable, 3) assess environmental factors influencing artists' sense of place, 4) analyze the relationship between artists' sense of place and involvement in conservation, and 5) explore institutional arrangements for integrating artists' sense of place from environmental aesthetic experiences into natural resources conservation planning.

Using a mixed methods approach, findings reveal that artists possess a strong sense of place grounded in Masbate City's natural environment, which inspires not only their artistic expression but also their participation in community and cultural endeavors, especially local festivals. Elements of environmental aesthetics, particularly diversity and richness, visual interest and exploration, and spatial characteristics, are significantly associated with local aesthetically remarkable natural sites. Notably, a pattern emerged, wherein more accessible natural sites were significantly associated with at least one element, while those less accessible showed no significant associations, indicating an accessibility distinction in shaping artists' aesthetic experiences. In terms of environmental factors influencing artists' sense of place, only the Bantigue Coast showed a significant influence. However, despite being the origin of Masbate City's main cultural asset, the Lapay Bantigue folk dance, it was found to diminish place attachment instead. Nevertheless, sites such as Masbate Social Park and Bugsayon Marine Sanctuary were suggestively linked to place identity and dependence. Meanwhile, unregulated land use change was significantly identified as a major threat to local artists' sense of place. Furthermore, artists' place identity. attachment, and dependence were significantly associated with their support for conservation to protect their artist identity, for using their art for conservation, and for using conservation to protect sites that inspire their art. Lastly, the study underscores how local government autonomy and cultural policies can facilitate institutional arrangements that include and empower artists in conservation planning.

This study advocates for natural resources conservation grounded in place-based and cultural values. It recommends enhancing access to aesthetically remarkable natural sites without causing ecological harm, protecting key habitats, promoting art-based biodiversity education, and recognizing natural sites with cultural value in land use plans. It also emphasizes the need for multi-agency collaboration, institutionalized artist participation, and integration of environmental aesthetics into local planning instruments, ensuring that conservation strategies are both ecologically sound and culturally resonant. This research contributes empirical insights into creative place-making and affirms the value of integrating environmental aesthetics and cultural perspectives into natural resources conservation.
Thesis
Keywords: Conservation of natural resources -- Philippines -- Masbate City; Nature (Aesthetics) -- Philippines -- Masbate City